PENDAMPINGAN TEKNIK KOLASE DI ATAS TAS SERUT UNTUK ANAK-ANAK SEKOLAH MINGGU GEREJA PANDU BANDUNG - Ariesa Pandanwangi; Dewi Isma Aryani; Belinda Sukapura Dewi; Rosida Tiurma Manurung; Ida Ida; Basituasi Baene (LPPM Universitas Bina Bangsa, 2023)
Pandu Church Sunday School is located at Jalan Pandu No.4, Pamoyanan, Cicendo District, Bandung. This school has creativity programs that aim to improve children's character in working together or having empathy in solving a problem that is being faced. To develop this character requires various efforts related to creativity. The problems faced by partners require strategies for solving them, one of which is assistance in making pictures using the collage technique on drawstring bags that students can use every day. The aim is to improve the skills that are expected to be able to develop their character in the future. The method used is a mentoring method involving students. Participants totaled 27 people. As a result, participants can draw with mixed media, the chosen theme is family and the environment such as flora and fauna. The visualized composition varies from asymmetrical and centered. The colors combined are very interesting, many children choose flannel in primary colors such as red, yellow, blue, orange